A comparison of the European Society of Cardiology, the Seattle and the Refined Criteria for interpreting the athlete's ECG in a pre-participation screening programme. Issue 6 (1st December 2016) - De Vos, Laurens; De Sutter, Johan
Abstract : Objective Sudden cardiac death is the main cause of non-traumatic mortality in young athletes. It is mainly caused by asymptomatic structural or electrical heart disease. This indicates the potential need for a pre-participation screening programme. Adding a 12-lead resting ECG to a cardiovascular screening programme increases sensitivity, but reduces specificity. ECG-interpretation criteria have been proposed in order to improve specificity and cost-efficiency. This review evaluates three frequently used criteria and their effect on the sensitivity and specificity of a pre-participation screening programme. Methods and results This non-systematic review assesses the data of four recent studies comparing the European Society of Cardiology (ESC), the Seattle and the Refined Criteria in a pre-participation screening programme. The sensitivity and specificity of the criteria are evaluated in young (< 35 years) Caucasian, Arabic and black athletes. There is no significant difference in sensitivity between the three criteria (98.1% - 100%). The Refined Criteria are more specific than the ESC and the Seattle criteria. The specificity of the ESC recommendations ranged from 64.8% to 76.6% and the specificity of the Seattle criteria ranged from 87.5% to 88.8%. The Refined Criteria have the highest specificity, 91.4% to 94.0%. Applying the Refined Criteria results in a significant decrease in abnormal ECGs and an improvement of the positive predictive value of an abnormal ECG. Conclusions Applying the Refined Criteria results in a significant increase in specificity when compared to the ESC and the Seattle criteria, while retaining the same sensitivity. This reduces the amount of abnormal ECGs from 12.7% - 22.3% with the ESC criteria to 1.9% - 6.6% with the Refined Criteria, which in turn greatly decreases the need for further investigations and thus the costs of a pre-participation screening programme.